External Examiner’s Report for the 4th Year Medical Examination in Forensic Medicine: Is It A Magician With a Wand? - B Meel (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Externalexaminers are generally considered people of integrity, and honesty. The right to pass or fail students is within their discretion. The examination report that they produce must be congruent with their actions. The post examination comment by the external examiner for the 4th year medical examination in Forensic Medicine stating that students were weak in Forensic Medicine was not consistent, however, with the marks he awarded to the students. Objective: To validate the report of external examiner with his action. Method: Every year an external examiner is invited to conduct an examination of 4th year MB. ChB students in Forensic Medicine. There were three specialist examiners who conducted an examination of medical students. The external examiner (Mr. X) has been invited from a pioneer institute for the last three years. Mr. X also made changes, and approved course contents at the beginning of the year. Results: There were 97 students who sat for the examination. Of these, 93 (96%) passed and none of them failed. Only 4% were required to write a supplementary examination. All scripts were marked by all three examiners. One third of the students (31/32%) who received the lowest marks were exposed to the external examiner for an oral examination, together with their scripts. The external examiner made no change of marks in six cases. Of the other 24 students, six students marked were decreased up to 4%, while the remaining 18 students’ marks were increased by up to 20%20%. One student has awarded a distinction (75%) by the external examiner (increased from 55% to 75%). Conclusion: The comment of an external examiner was, however, not congruent with his actions. Therefore, the external examiner is a magician, but without a magic wand.